2008
DOI: 10.1242/jcs.031286
|View full text |Cite
|
Sign up to set email alerts
|

BMP2 induction of actin cytoskeleton reorganization and cell migration requires PI3-kinase and Cdc42 activity

Abstract: group I and group II PAK isoforms as well as LIMK1 with similar kinetics to Cdc42 or PI3K activation. BMP2 activation of PAK and LIMK1, measured by either kinase activity or with antibodies raised against phosphorylated residues at their activation loops, were abolished by blocking PI3K-signaling pathways. Together, these findings suggest that Cdc42 and PI3K signals emanating from BMP receptors are involved in specific regulation of actin assembly and cell migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
114
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 62 publications
(86 reference statements)
8
114
1
Order By: Relevance
“…For example, it has been shown that BMP2 enhances the motility of prostate cancer cells via activation of integrins (30) and affects actin cytoskeleton reorganization and cell migration through regulation of phosphatidylinositide 3-kinase and cell division control protein 42 activity (40). Effects on LIM kinase 1 (LIMK), a key regulator of actin dynamics, which phosphorylates and inactivates cofilin, an actin depolymerizing factor, have also been reported (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that BMP2 enhances the motility of prostate cancer cells via activation of integrins (30) and affects actin cytoskeleton reorganization and cell migration through regulation of phosphatidylinositide 3-kinase and cell division control protein 42 activity (40). Effects on LIM kinase 1 (LIMK), a key regulator of actin dynamics, which phosphorylates and inactivates cofilin, an actin depolymerizing factor, have also been reported (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Two additional SMADs are known as inhibitory SMADs, SMAD6 and SMAD7. Furthermore, BMPs can also activate noncanonical, SMAD-independent pathways, mainly MAPK pathways (Erk, p38), the LIMK pathway, or the PI3K pathway, which are also involved in osteoblast differentiation (Shi & Massague 2003, Gamell et al 2008, Ulsamer et al 2008, Ortuno et al 2010.…”
Section: The Interplay Between Mirnas and Bmp Signalingmentioning
confidence: 99%
“…Sotobori et al (2006) suggested that BMP-2 promotes the migration of osteosarcoma cells through fibronectin-integrin β1 signaling, and Lai et al (2008) reported that BMP-2 promotes the migration of prostate cancer cells by activating integrins β1 and β3. Recently, Gamell et al (2008) proposed that BMP-2 influences the reorganization of the cytoskeleton by activating PI3K and Cdc42 of the Rho GTPase superfamily and its downstream molecules (PAK1, LIMK1, etc. ), so as to regulate cell migration further.…”
Section: Discussionmentioning
confidence: 99%